C2‐Symmetric Bicyclic Bisborane Catalysts: Kinetic or Thermodynamic Products of a Reversible Hydroboration of Dienes - Tu, Xian‐Shuang; Zeng, Ning‐Ning; Li, Ru‐Ye; Zhao, Yu‐Quan; Xie, De‐Zhen; Peng, Qian; Wang, Xiao‐Chen (Angewandte Chemie International Edition, 2018)
We prepared a new class of chiral C2‐symmetric bicyclic bisborane catalysts by addition reactions of internal dienes with the Piers borane, HB(C6F5)2, and an analogue, HB(p‐C6F4H)2. The dependence of the addition pattern on the reaction temperature allowed us to selectively prepare two diastereomeric catalysts from a single diene precursor. The bisboranes prepared in situ exhibited excellent activity (turnover numbers up to 200 at −40 °C) and enantioselectivity (up to 95 % ee) in imine hydrogenation reactions. B,B bicycles: A new class of C2‐symmetric bicyclic bisborane catalysts was synthesized by treating bicyclic dienes with HB(C6F5)2 or HB(p‐C6F4H)2. Remarkably, two diastereomeric catalysts could be accessed selectively from a single diene precursor by simply varying the reaction temperature (see scheme). These catalysts exhibited excellent activity and selectivity in the hydrogenation of imines.